Validity Evidence of an Epidemiological Oropharyngeal Dysphagia Screening Questionnaire for Older Adults - Hipólito Virgilio Magalhães Junior; Leandro de Araújo Pernambuco; Renata Veiga Andersen Cavalcanti; Kenio Costa Lima; Maria Angela Fernandes Ferreira (Clinics, 2020)
OBJECTIVE: This research aimed to identify evidence of validity of a self-reported Oropharyngeal Dysphagia screening questionnaire for older adults based on test content, response processes, internal structure, relations to other variables, and reliability. METHOD: This is a nonrandomized, cross-sectional study employing the concepts and principles of the Standards for Educational and Psychological Testing. Data were collected from 644 community-dwelling older adults (both genders, age: ≥60 years) who agreed to participate in some steps of the validation process. Statistical methods obtained the content representation of the construct, internal structure validation, discriminant and convergent evidence, and reliability, using a 5% significance level. RESULTS: The screening tool was re-specified in nine questions that provided the best fit and robust reliability, with proper discriminant and convergent evidence. CONCLUSIONS: The screening questionnaire presented valid and reliable results to identify oropharyngeal dysphagia symptoms in older adults, highlighting the importance of the validation process based on the standards to construct an epidemiological instrument.